1984
DOI: 10.1007/bf02618875
|View full text |Cite
|
Sign up to set email alerts
|

Comparative use of fructose and glucose in human liver and fibroblastic cell cultures

Abstract: The effect of fructose as a substitute for glucose in cell culture media was investigated in human skin fibroblast and liver cell cultures. Cells were grown for between 2 and 10 days in identical flasks in four different media, containing 5.5 mmol X 1-1 and 27.5 mmol X 1-1 glucose and fructose, respectively. In the presence of fructose, cell growth was stimulated, but less in liver cells than fibroblasts. At Day 6, increases were observed in [3H]thymidine incorporation, protein levels, and amino acid consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
3
6
1
Order By: Relevance
“…This observation is in line with the finding that hyperglycemia per se does not impair leukocyte chemotaxis [32]. Previous in vitro studies have shown that high glucose concentration increases fibroblast proliferation [35,36], collagen synthesis [37] and protein synthesis [38]. In the present in vivo experiment no such effect could be seen and this is concordant with findings that local hyperalimentation of granulation tissue with various nutrients enhances wound healing [39], but hy-peralimentation with glucose alone does not [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in line with the finding that hyperglycemia per se does not impair leukocyte chemotaxis [32]. Previous in vitro studies have shown that high glucose concentration increases fibroblast proliferation [35,36], collagen synthesis [37] and protein synthesis [38]. In the present in vivo experiment no such effect could be seen and this is concordant with findings that local hyperalimentation of granulation tissue with various nutrients enhances wound healing [39], but hy-peralimentation with glucose alone does not [40].…”
Section: Discussionsupporting
confidence: 93%
“…Previous cell culture studies have demonstrated that elevated fructose concentrations increase fibroblast proliferation and protein synthesis [35,36]. However, in our in vivo experiment the only detectable significant change was a decreased accumulation of nitrogen in the group treated with 1 M fructose suggesting diminished protein synthesis.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, at day 3 or day 6, the protein levels were not significantly different in the control and HFI cells, whatever the medium used. (Delhotal et al, 1984). The time courses of the uptakes of the two hexoses were the same for the two types of cell cultures.…”
Section: Protein Synthesismentioning
confidence: 79%
“…To test this latter hypothesis further, cells of the hepatocyte lineage (HepG2 hepatoma) were examined to assess if D-Fuc could enhance NO-mediated 59 Fe release. In contrast to fibroblasts, hepatocytes can readily metabolize D-Fuc (45), and using the HepG2 cell line this monosaccharide acted similarly to D-Glc, increasing NO-mediated 59 Fe release to a level 3-fold greater than that observed in its absence (data not shown). This experiment again indicated that metabolism of the monosaccharide was essential for increasing NO-mediated 59 Fe release.…”
Section: The Effect Of Monosaccharides and Disaccharides On Nomediatementioning
confidence: 92%
“…Statistical analysis of the results from seven experiments showed that the addition of D-Man to GSNO significantly increased (p Ͻ 0.0006) 59 Fe release compared with GSNO alone. It is relevant to note that D-Man can be metabolized by fibroblasts (43,44), whereas D-Fuc is poorly metabolized (45). To determine whether the effects observed with D-Glc and D-Man were specific to these monosaccharides, a wide variety of different aldohexoses, aldopentoses, ketohexoses, and disaccharides were examined for their ability to enhance NO-mediated 59 Fe mobilization.…”
Section: The Effect Of Monosaccharides and Disaccharides On Nomediatementioning
confidence: 99%